2015
DOI: 10.1128/jcm.00323-15
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Serotype Determination Utilizing High-Throughput Genome Sequencing Data

Abstract: f Serotyping forms the basis of national and international surveillance networks for Salmonella, one of the most prevalent foodborne pathogens worldwide (1-3). Public health microbiology is currently being transformed by whole-genome sequencing (WGS), which opens the door to serotype determination using WGS data. SeqSero (www.denglab.info/SeqSero) is a novel Webbased tool for determining Salmonella serotypes using high-throughput genome sequencing data. SeqSero is based on curated databases of Salmonella serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
320
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(330 citation statements)
references
References 36 publications
8
320
1
1
Order By: Relevance
“…Importantly, since the frequency of nontypeability of in vitro serotyped P. aeruginosa isolates may amount to Ͼ65% (10), analysis with PAst is clearly advantageous and superior compared to conventional in vitro serotyping. Importantly, the superiority of the PAst tool as a reliable and fast typing method is consistent with that of other published tools for in silico serotyping (31)(32)(33)(34)(35). Similar to SerotypeFinder (in silico serotyping of Escherichia coli) (31), LisSero (in silico serotyping of Listeria monocytogenes) (34,35), and SeqSero (in silico serotyping of Salmonella) (32), PAst resolves the OSA cluster information to the most accurate typing possible as a serogroup representing 1 to 3 serotypes.…”
Section: Discussionsupporting
confidence: 51%
“…Importantly, since the frequency of nontypeability of in vitro serotyped P. aeruginosa isolates may amount to Ͼ65% (10), analysis with PAst is clearly advantageous and superior compared to conventional in vitro serotyping. Importantly, the superiority of the PAst tool as a reliable and fast typing method is consistent with that of other published tools for in silico serotyping (31)(32)(33)(34)(35). Similar to SerotypeFinder (in silico serotyping of Escherichia coli) (31), LisSero (in silico serotyping of Listeria monocytogenes) (34,35), and SeqSero (in silico serotyping of Salmonella) (32), PAst resolves the OSA cluster information to the most accurate typing possible as a serogroup representing 1 to 3 serotypes.…”
Section: Discussionsupporting
confidence: 51%
“…Despite the obstacles, WGS remains an improvement to current S. Enteritidis characterization methods and may become an even more attractive option as costs decrease. As WGS becomes faster and less expensive for public health laboratory use, in addition to subtyping, it can replace other phenotypic characterization methods, such as serotyping and antibiotic resistance testing (47).…”
Section: S Enteritidis Became a Significant Source Of Illness In Thementioning
confidence: 99%
“…The sequence showed that the isolate belonged to ST34 (Larsen et al, 2012), an expanding multiresistant clone (Sun et al, 2014;Wong et al, 2013), had a 4 : i : 1,2 predicted serotype (Zhang et al, 2015), and contained several metal resistance genes and genes for enterobactin and aerobactin production. A second integron was detected, as well as additional antibiotic resistance genes: bla TEM1-A , aac(3)-IIa, aac(6')Ib-cr, aadA2, catA, sul1, sul3, dfrB1 and tet(B) (Zankari et al, 2012).…”
mentioning
confidence: 99%